Aquatic living resources Vol 8 No 4 7995 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
This issue gathers together a selection of papers presented at the international workshop on the Biological Bases forAquaculture of Siluriformes (BASIL) held at Montpellier from 2427 May, 1994 for which CTA provided part of the funding.The papers...